TINGKAT KESADARAN MASYARAKAT TEGAL DALAM BERASURANSI - Gunistiyo, M.Si., Drs.; bekti, Su (SOSEKHUM, 2006)
This research is purposed to recognize asurance are grade of Tegal people and torecognize correlation care grade. The method which is applied in this research is survai method.Collecting data is done by quesionair andinterview. To test people care in having asurance inTegal is used index rate. While to test correlation among education and people income withasurance care grade is used chi square (l2) test.From the analysis is quoted the result that people care in asurance in Tegal is in lowgrade and there is significant correation in valueing for asurance based on education grade ofTegal people and also incomegrade of Tegal people.Key word : recognize asurance.